A New Second Derivative Free Iterative Method of Fifth Order of Convergence and Its Applications - Putri, Ayunda; M, Imran (Jurnal Matematika UNAND, 2023)
The primary objective of this article is to derive a new free from second derivative iterative method for solving nonlinear equations. The proposed method is proven to have fifth order of convergence. Comparisons with other iterative methods represent the advantage of the modified method. Observation on applications of the method in problem of chemical equilibrium , binary azeotropic problem, volume from van der Waals equations and eccentric anomaly in Kepler's law exhibits that our method is applicable and preferable.